Evaluation of cytotoxic and apoptotic effects of the extracts and phenolic compounds of Astragalus globosus Vahl and Astragalus breviflorus DC - Benan Kalaycı; Nihal Şimşek Özek; Ferhunde Aysin; Hilal Özbek; Cavit Kazaz; Mehmet Önal; Zühal Güvenalp (Saudi Pharmaceutical Journal, 2023)
Astragalus L. is a genus member of the Fabaceae family, representing about 3,000 species all over the world and 380 species in Turkey. Astragalus species have been used in traditional medicine for many years. Astragalus globosus Vahl, known as “top geven”, is a dwarf, scapose, perennial herb, Astragalus breviflorus DC., known as “yünlü geven”, is an extremely spiny dwarf shrub. These endemic species grow in the Turkish cities of Erzurum, Kars, and Van. This is the first phytochemical and cytotoxic investigation of Astragalus globosus Vahl and Astragalus breviflorus DC. The main extracts and sub-fractions from the plants were evaluated for in vitro cytotoxic and apoptotic activities. The IC50 values of dichloromethane, n-butanol, and water extracts of the aerial parts of A. globosus against the MCF-7 cell line were determined as 28.39, 868.60, and 1753.00 µg/mL. The values for the MDA-MB-231 cell line were 264.00, 620.30, and 1300.50 µg/mL, respectively. From A. globosus, the following were isolated: a flavone glycoside, diosmetin-7-O-rutinoside (1); and two flavonol glycosides, isorhamnetin-3-O-rutinoside (2) and quercetin-3-O-galactoside (3). From A. breviflorus, two phenolic acids, caffeic acid (4) and chlorogenic acid (5), and a flavan-3-ol, catechin (6), were isolated. Diosmetin-7-O-rutinoside was isolated from Astragalus species for the first time and showed the highest cytotoxic activities on the MCF-7 and MDA-MB-231 breast cancer cell lines with IC50 values of 13.65 and 12.89 μg/mL, respectively. Moreover, we observed that diosmin exerts cytotoxic effects by causing cell necrosis.